HUBUNGAN PERSEPSI SISWA SMA NEGERI 1 ARGA MAKMUR TERHADAP PENCEGAHAN COVID-19 - Rendri Bayu Hansah; Nurwiyeni, Nurwiyeni; Yanti Fitriyasa; Yosserizal, Yosserizal; Dinda Trifa Chintia (Nusantara Hasana Journal, 2023)
Since it first appeared at the end of 2019, the Novel coronavirus disease 19 (COVID-19) was officially declared a global pandemic by the World Health Organization (WHO) on March 11, 2020 and WHO urges the government to oblige its people to implement protective behavior to prevent transmission and the spread of COVID-19. Before making an action, humans tend to perceive something as good or positive perceptions or negative perceptions that will influence their actions and based on the Health Belief Model (HBM), people will change their behavior if they understand that the disease is serious, otherwise they may not switch to behavior which is healthy. Methods: This type of research is a correlative analytic study with a cross-sectional approach. The affordable population in this study were students of SMA Negeri 1 Arga Makmur Bengkulu Utara with 267 samples. Univariate data analysis is presented in the form of frequency distribution and percentage and bivariate analysis using the kruskall-wallis test and data processing using a computerized SPSS version 25.0 program. The most respondents were female, namely 178 people (66.7%), the most respondents with a sufficient perception of vulnerability were 194 people (72.7%), the most respondents with a good perception of severity were 147 people (55.1% ), the most respondents with a good perceived benefit were 217 people (81.3%), the most respondents with a sufficient perception of obstacles were 212 people (79.4%), the most respondents with a good perception of cues were 227 people (85.0 %), and the most respondents with a good self-efficacy perception were 231 people (86.5%), the most respondents had a good attitude, namely 166 people (62.2%), there was a relationship between perceptions of vulnerability of students of SMA Negeri 1 Arga Makmur to attitudes. prevention of COVID-19 (p = 0,000), there is no relationship between the perception of severity of SMA Negeri 1 Arga Makmur students on attitudes to prevention of COVID-19 (p = 0.077), there is a relationship between perceived benefits of students of SMA Negeri 1 Arga Makmur on attitudes towards preventing COVID-19 (p = 0.012), there is a relationship the perception of barriers of SMA Negeri 1 Arga Makmur students towards attitudes towards prevention of COVID-19 (p = 0,000), there is a correlation between the perception of cues of SMA Negeri 1 Arga Makmur students on attitudes to prevention of COVID-19 (p = 0,000) and there is a correlation between the perception of self-efficacy of high school students Negeri 1 Arga Makmur on the attitude of preventing COVID-19 (p = 0,000). There is a relationship between perceptions of vulnerability, perception of barriers, perception of cues, perceived benefits and perceptions of self-efficacy and there is no relationship between perceptions of severity of SMA Negeri 1 Arga Makmur students on attitudes to prevention of COVID-19.